Sejarah Kalender Hijriyah - Muhajir Muhajir (CV. ULIL ALBAB CORP, 2024)
This Study or discussion to talk about the history of the birth of Hijri Calendar (al-al-Hijri calendar) among Muslims. On the 1st of Muharram, Muslems commemorating their New Year Hijri or Islamic New Year. Researching history dating Arabs of pre-Islamic period up to the reign of Umar bin Khattab with the birth of Hijri Calendar. When the Prophet was alive, Muslims can ask all religious matters to him, but at the time he passed away, the friends or ulama trying to interpret Islamic religious teachings. Historically, pre-Islamic Arabs used Qamariyah-Syamsiyah calendar system (luni-solar). This calendar system requires intercalation or adding one month to adjust Qamariyah with Syamsiyah. However, no agreement in the placement of the years that had made their break with tradition intercalation Abraham, respecting and forbidden to do battle in the months noble (al-asyhur al-Hurum), namely Qa`dah, Dzu al-Hijjah, Muharram and Rajab. They were still fighting in the month of Muharram, for example, because it as month 13 (intercalation). This lasted until the Prophet Hijrah to Medina. The fall of al-Tawbah/9: 36-37 Syamsiyah-stop calendar system and replace it with Qamariyah Qamariyah pure (lunar). Until the Prophet's death (11 H/634 AD), the Arabs use Qamariyah calendar system, without the year. They only know the name of the day, month and date. In the reign of Umar bin Khattab (13-23 H/634-644 M), exactly 17 years H/637 M, he defined as the Hijri Calendar Islamic government official calendar. The proposal submitted by the beginning of the calendar creation of Abu Musa al-Ash'ari (governor of Kufa). The Prophet's hijrah year chosen as the first year as the proposal of Ali ibn Abi Talib, while selected as the first month Muharram is proposed Uthman bin al-Affan. In the determination to Hijri Calendar, choice of Muharram as the first month of the year motivated by political considerations.